Website Work Quality Assessment to Improve Webometrics Rank on the Website of https://uin-suka.ac.id/ - Rama Kertamukti; Mochamad Sodik; B J Sujibto (Jurnal Pewarta Indonesia, 2021)
UIN Sunan Kalijaga is one of the State Islamic Universities that applies website media as a medium to provide information to users both for the academic community and the general public who want to know information related to information about campus, one of which is news information, registration, announcements and so on. The strength of the website becomes a measuring tool in determining rankings in Webometrics. The purpose of ranking or webometrics (https://www.webometrics.info/) is to promote the publication of the website. Supports Open Access, electronic access to scientific publications and other academic materials. This article tries to explain the website visibility of UIN Sunan Kalijaga Yogyakarta as an effort to increase webometrics ranking. This study uses a qualitative approach with a descriptive type, by analyzing information sources, website structure and technology with bibliometric and infometric approaches used by the website of UIN Sunan Kalijaga Yogyakarta. The results of the analysis obtained by measuring the usability element, the uin-suka.ac.id website shows the uin-suka.ac.id website looks quite "friendly" to use on mobile phones or smartphones that access the uin-suka.ac website. en. Analysis of Information Quality shows that the uin-suka.ac.id website does not yet have good backlinks. The quality of service interactions perceived by users of the uin-suka.ac.id website does not appear to have produced a good enough impression in their trust and empathy activities in the access process, such as in terms of transactions and information security, message delivery, personalization and communication activities.